2001
DOI: 10.1068/p3025
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Visual and Auditory Temporal Processing in Reading Irregular and Nonsense Words

Abstract: In the present study, the role of rapid visual and auditory temporal processing in reading irregular and nonsense words was investigated with a group of normal readers. One hundred and five undergraduates participated in various visual and auditory temporal-processing tasks. Readers who primarily adopted the phonological route in reading (nonsense-word readers) showed a trend for better auditory temporal resolution but readers who primarily adopted sight word skills (irregular-word readers) did not exhibit bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 48 publications
(74 reference statements)
2
21
1
Order By: Relevance
“…The order of the presentation of the conditions was counterbalanced. As was stated in the introduction, visual temporal processing is more closely related to irregular words (Au & Lovegrove, 2001a). Visual temporal acuity also plays a role in a reading condition that requires saccadic eye movement (Chase et al, 2003;Hill & Lovegrove, 1992;Pammer et al, 2004).…”
Section: Measure 1b: Vgapmentioning
confidence: 88%
See 2 more Smart Citations
“…The order of the presentation of the conditions was counterbalanced. As was stated in the introduction, visual temporal processing is more closely related to irregular words (Au & Lovegrove, 2001a). Visual temporal acuity also plays a role in a reading condition that requires saccadic eye movement (Chase et al, 2003;Hill & Lovegrove, 1992;Pammer et al, 2004).…”
Section: Measure 1b: Vgapmentioning
confidence: 88%
“…Such differences might be more obvious in irregular words than in pseudowords, given their orthographic characteristics (Au & Lovegrove, 2001a).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is the magnocellular and subsequent dorsal stream processing that most likely generates the speeded function needed [20]. Nonword reading on the other hand does not place as much demand on quick visual recognition but rather depends more on auditory temporal processing [19]. A dorsal stream processing component may, however, play a significant role in nonword reading.…”
Section: Discussionmentioning
confidence: 92%
“…More specifically, these results are consistent with previous reports that a visual temporal processing component underlies aspects of orthographic decoding. For example, a group of skilled adult readers, similar to the participants examined in the current study [19], demonstrated that responses to 12 Hz flicker frequencies were highly correlated with irregular word reading. Moreover, this relationship could not be explained by reading style, defined by an individual's relative strength in either orthographic or phonological decoding.…”
Section: Discussionmentioning
confidence: 99%